Pengaruh Kepemilikan Institusional, Struktur Modal, Komite Audit dan Ukuran Perusahaan terhadap Profitabilitas : Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar pada Bursa Efek Indonesia Periode 2019–2023 - Rayhanna Fadilla; Roza Fitriawati (Jurnal Riset Akuntansi, 2024)
This research aims to determine the influence of institutional ownership, capital structure, audit committee and company size on profitability in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2019 - 2023 period as many as 138 companies. The data used in this research was obtained from financial report data. The population in this study are food and beverage sector companies listed on the Indonesia Stock Exchange. The sampling technique used was the purposive sampling method and 190 sample data were obtained from 38 companies. The analysis technique used in this research is a multiple linear regression analysis test using the Statistical Package for the Social Sciences (SPSS) program. The results of this research show that the Institutional Ownership, Capital Structure and Company Size have a positive and significant effect on profitability, while the Audit Committee has no effect on profitability